Density in liquid - University of South Florida, Dept. of Chemistry; Human Relations Media, inc. (Chatworths, CA.: AIMS)
Presents chemistry in a situational format, using household chemicals. Numerous scenes depict chemical reactions, such as a density gradient made with alcohol, water, and oil, in order to help the student comprehend the relevance of chemistry to everyday life
Intermediate grades through high school students
Keywords: Liquids